The Weaving is Us: Decolonizing the Tools for the Feminist Imagination - Diaz-Diaz, Claudia; Harris, Dorothea; Harris, Thea (International Journal for Talent Development and Creativity, 2024)
This article documents weaving as a decolonizing epistemic tool for feminist futures that emerges from the work of our collective – the Feminist Imaginary Research Network. As a collective of feminist adult educators who work in both the academy and women’s museums, weaving challenges the centrality of rationality over other ways of knowing and being. Following the teachings of Indigenous women thinkers and artists, including the work of some of our members, we frame weaving as an epistemic tool and aesthetic language for future-making. Weaving acts upon us as a mirror of our history, as an antidote against the supremacy of rationality, and as a tool for collective projects of transformation. As a decolonizing tool, weaving gathers us around Indigenous women’s traditional knowledge, but also confronts us with the question of our obligations when the teachings of weaving have been offered to us – what is our responsibility to the work, to each other, and to this emergent knowledge?